USE OF JSM-METHOD TO FIND REGULARITIES OF THE ROAD ACCIDENTS RISING - Poletaykin, О.; Kostenko, А.; Полєтайкін, О. М.; Костенко, А. В.; Полетайкин, А. Н.; Костенко, А. В. (Харьковский национальный автомобильно-дорожный университет, 2015)
The use of the JSM-method for problem solving of determining regularities of traffic accident occurrance resulting in injured participants is considered. As a solution of the problem they proposed the cause-and-effect relationship system, which makes it possible to develop solutions directed to impove the traffic safety on the motorroads of Ukraine.
ЗАСТОСУВАННЯ ДСМ-МЕТОДУ ДЛЯ ПОШУКУ ЗАКОНОМІРНОСТЕЙ ВИНИКНЕННЯ ДОРОЖНЬО-ТРАНСПОРТНИХ ПРИГОД
ПРИМЕНЕНИЕ ДСМ-МЕТОДА ДЛЯ ПОИСКА ЗАКОНОМЕРНОСТЕЙ ВОЗНИКНОВЕНИЯ ДОРОЖНО-ТРАНСПОРТНЫХ ПРОИСШЕСТВИЙ
Keywords: registration card of an accident; cause-and-effect relationship; data extraction; generation of hypotheses; intelligent analysis of accidents; карта обліку ДТП; причинно-наслідковий зв’язок; збір даних; визначення закономірностей виникнення ДТП; інтелектуальний аналіз аварійності; карта учета ДТП; причинно-следственная связь; извлечение данных; определение закономерностей возникновения ДТП; интеллектуальный анализ аварийности; 343.346.2